Research and development project selection via IF-DEMATEL and IF-TOPSIS - (:unkn) unknown (Springer Verlag, 2020)
Research and development (R&D) project selection plays a fundamental role for the success of the enterprises. The evaluation of R&D projects in both production and service sectors is considered as a multi-criteria decision making (MCDM) problem since it contains several conflicting criteria. Based on the nature of the decision-making process, uncertainty and vagueness originate from the human judgments. In order to deal with this problem, intuitionistic fuzzy sets (IFSs) which are capable of overcoming ambiguity in decision-making process are handled. Firstly, IF-DEMATEL was utilized to illustrate the relationships between criteria and to remove inefficient criteria. Afterwards, by using the selected effective criteria, most appropriate alternative is found by using IF-TOPSIS. A numerical example was introduced to demonstrate the steps of the proposed approach. © 2020, Springer Nature Switzerland AG.
Keywords: IF-DEMATEL; IF-TOPSIS; R&D project selection